2021
DOI: 10.1101/2021.09.11.21263428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interrogating COVID-19 Vaccine Hesitancy in the Philippines with a Nationwide Open-Access Online Survey

Abstract: To mitigate the unprecedented health, social, and economic damage of COVID-19, the Philippines is undertaking a nationwide vaccination program to mitigate the effects of the global pandemic. In this study, we interrogated COVID-19 vaccine hesitancy in the country by deploying a nationwide open-access online survey, two months before the rollout of the national vaccination program. The Health Belief Model (HBM) posits that people are likely to adopt disease prevention behaviors and to accept medical interventio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A recent preprint by Caple et al reported the initial results of an online survey conducted in January 2021 that involved 7193 respondents, which showed an overall rate for COVID-19 vaccine acceptance of 62.5%. 78…”
Section: Philippinesmentioning
confidence: 99%
“…A recent preprint by Caple et al reported the initial results of an online survey conducted in January 2021 that involved 7193 respondents, which showed an overall rate for COVID-19 vaccine acceptance of 62.5%. 78…”
Section: Philippinesmentioning
confidence: 99%
“… 24 Studies from the Philippines and Indonesia revealed that perceptions of being susceptible and having more severe disease after being infected and perceived efficacy and benefits of the COVID-19 vaccines were predictors for vaccine acceptance. 21 , 25 Studies in Bangladesh, Pakistan and the United Arab Emirates also showed similar patterns. Among university students in Bangladesh, those without a previous COVID-19 infection, poorer knowledge related to COVID-19, and negative perceptions and attitudes toward the vaccine were significantly associated with vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 64%
“…The brand that obtained the highest weighted mean was the Pfizer-BioNTech (3.11) from the USA and Germany as presented in Table 5. The result was supported by the news from [39], [40]. There are only 19% of Filipinos were eager to be vaccinated, with the highest level of trust in vaccinations from the United States (41%) [39].…”
mentioning
confidence: 85%